2005
DOI: 10.1007/s10295-005-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Simple oligomers as antimicrobial peptide mimics

Abstract: New approaches to antibiotic design are desperately needed. The design of simple oligomers that capture the shape and biological function of natural antimicrobial peptides could prove to be versatile and highly successful. We discuss the use of aromatic backbones to design facially amphiphilic (FA) beta-sheet like structures which are potently antimicrobial. These oligomers capture the physiochemical properties of peptides like the Magainins and Defensins, which fold into specific conformations that are amphip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…In this test, treated polymer was shaped into plates and polymer surfaces were held in contact with bacterial cell suspension (10 6 CFU/mL) using sterile cover and kept for 24 h in humid conditions at 37 °C. The number of viable cells was counted after plating on agar and expressed in colony forming units per milliliter (CFU/mL) Tew and coworkers tested the activity of AMMs incorporated in PU coatings by spraying the samples with E. coli followed by immersion in bacterial growth media for 72 h [67]. Microscopy showed that the untreated sample (left) is significantly colonized while the treated sample (right) does not support E. coli growth (Fig 18).…”
Section: Methods For Evaluating Efficiency Of Biocidal Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this test, treated polymer was shaped into plates and polymer surfaces were held in contact with bacterial cell suspension (10 6 CFU/mL) using sterile cover and kept for 24 h in humid conditions at 37 °C. The number of viable cells was counted after plating on agar and expressed in colony forming units per milliliter (CFU/mL) Tew and coworkers tested the activity of AMMs incorporated in PU coatings by spraying the samples with E. coli followed by immersion in bacterial growth media for 72 h [67]. Microscopy showed that the untreated sample (left) is significantly colonized while the treated sample (right) does not support E. coli growth (Fig 18).…”
Section: Methods For Evaluating Efficiency Of Biocidal Surfacesmentioning
confidence: 99%
“…Tew and coworkers incorporated AMMs into polyurethane (PU) coatings which showed excellent inhibition of E.coli growth on the surface despite immersion in rich growth media for 72 h [67]. More recently, AMM blended into medical grade catheter tubing prevented S. aureus growth completely even after repeated exposure.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…The quest for new and improved antimicrobial peptides has led to the study of peptide mimetics (30). Investigators in this field have developed a series of inexpensive nonpeptidic oligomers and polymers, modeled after compounds found in nature, that adopt amphiphilic secondary structures and exhibit potent and selective antimicrobial activity (25). Modifications of these molecules have resulted in the identification of small-molecule oligomers that have molecular masses ranging from 690 to 1,000 Da, that potently inhibit the growth of both gram-negative and gram-positive bacteria, and that exhibit low hemolytic activity (29).…”
mentioning
confidence: 99%
“…MIC values were determined by a modified method from literature [24,25]. The E. coli cells were diluted with a minimal medium (28 mM glucose, 42 mM Na 2 HPO 4 , 22 mM KH 2 PO 4 , 18.7 mM NH 4 Cl, 8.5 mM NaCl, 1 mM MgSO 4 , and 0.09 mM CaCl 2 at pH 7.2.…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%